2015
DOI: 10.1088/0964-1726/24/8/085016
|View full text |Cite
|
Sign up to set email alerts
|

Comparative performance of various smart aggregates during strength gain and damage states of concrete

Abstract: Information regarding the early strength gain of fresh concrete determines the time for the removal of form work and the transfer of pre-stressing forces for pre-stressed concrete. An ultrasonic based non-destructive evaluation of early strength gain may not work for concrete in fluid and semi-solid phases. A possible alternative is a lead zirconate titanate (PZT)-based smart aggregate embedded in concrete, which can evaluate the micro-structural and rheological properties right from the fluid phase. A set of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 22 publications
2
41
0
Order By: Relevance
“…The behavior of a concrete member can be classified into two states: an intact state (no damage occurrence) and a damage state (inner concrete damage, crack propagation, and failure). In the intact state, the impedance signals are changed rarely due to the prestress acting on the coated PZT (i.e., σ o 1 + σ o 2 ) [ 24 ]. When inner concrete cracks occur locally close to the coated PZT sensor, the prestress is partially released.…”
Section: Theoretical Model Of the Piezoelectric Sensor-embedded Smmentioning
confidence: 99%
See 2 more Smart Citations
“…The behavior of a concrete member can be classified into two states: an intact state (no damage occurrence) and a damage state (inner concrete damage, crack propagation, and failure). In the intact state, the impedance signals are changed rarely due to the prestress acting on the coated PZT (i.e., σ o 1 + σ o 2 ) [ 24 ]. When inner concrete cracks occur locally close to the coated PZT sensor, the prestress is partially released.…”
Section: Theoretical Model Of the Piezoelectric Sensor-embedded Smmentioning
confidence: 99%
“…When inner concrete cracks occur locally close to the coated PZT sensor, the prestress is partially released. This reveals that the boundary conditions surrounding the coated PZT are changed, resulting in rushed changes in the impedance responses of the embedded PZT sensors [ 24 , 40 ]. Figure 3 b illustrates the impedance responses of the PZT-embedded smart rock in a concrete member under compression.…”
Section: Theoretical Model Of the Piezoelectric Sensor-embedded Smmentioning
confidence: 99%
See 1 more Smart Citation
“…The performances of different types of smart aggregates were studied when they were embedded to monitor the strength gain of early age concrete. 22 Kim et al 23 demonstrated that a relationship can be established between the concrete curing status and the gradient of the susceptance spectrum measured from an embedded PZT. This approach could be advantageous since one no longer needs to identify the resonance peaks from the admittance signatures.…”
Section: Introductionmentioning
confidence: 99%
“…A comparitive study on the sensitivity of the EM admittance and structural mechanical impedance to damage in concrete structures was conducted. Saravanan et al compared the performance of various piezoceramic smart aggregates in the strength gain and damage states of concrete [ 4 ]. Yan et al used distributive piezoceramic smart aggregates to monitor the health status of a concrete shear wall during a destructive test [ 5 ].…”
Section: Introductionmentioning
confidence: 99%